KajianEkonomis Perencanaan Pengeboran Dan Peledakan Antara Kemitraan Dengan PT Bukit Asam (Persero) Tbk Pada Wilayah Pit II Banko Barat Di Tanjung Enim Sumatera Selatan: Economical Study of Drilling and Blasting planning Betweeen Partnership With PT Bukit Asam (Persero) Tbk The Pit Area II Banko West at Tanjung Enim South Sematera - Tampubolon, Amri; Tono, E.P.S.B Taman; Indriawati, Anisa (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2018)
In 2017 PTBA plans to open pit mining in Banko Barat Pit II uses a system of drilling and blasting. Drilling and blasting activities aimed memberai hard material to support the process of making material by excavator-unloading With limited human resources drilling and blasting is currently assisted by partners. To get the maximum benefit with minimum cost necessary to study the cost of drilling and blasting between using the cost of services partners or self-management tool by PTBA.Planning of drilling and blasting costs PTBA version used by the method of self-management tools while the costs of drilling and blasting use the services of the partnership using the mail service offering. Geometri blasting used method R.L Ash so that would be obtained comparative cost planning and drilling and blasting between PTBA and partner services.The cost of drilling obtained using a self-management tool values ​​obtained Rp 13.021.982.688/tahun, while using the services of the partnership obtained the value of Rp 26.472019.517/year. The cost of blasting using a self-management tool values ​​obtained Rp 44.767.919.566/year, while using the services of the partnership obtained the value of Rp 51.750.738.054/year. The total cost of drilling and blasting self-managed appliance obtained the value of Rp 57.789.902.254/year more economical compared with services partnership with a value of Rp 78.222.757.571/year, these results show the difference in cost of Rp 20.432.855.317/year.